Association between socioeconomic status with birth outcomes and infant growth in the first two years of life: case study in South Africa and democratic Republic of Congo - Ngandu, Christian Bwangandu (My University, 2020)
Background: Lower socioeconomic status has been associated with impaired child growth globally, but there have been limited literature and lack of consensus of the evidence on the relationship between socioeconomic status (SES) factors and infant growth in sub-Saharan Africa (SSA). Therefore, the aim of this thesis was to investigate the relationship between the household and maternal demographic as well as SES factors including maternal education; occupation; income; marital status; and household wealth index (HWI]), and adverse birth outcomes and infant undernutrition from birth until age two years in SSA. Methods: One theoretical and two empirical studies were conducted to achieve the aim of this thesis. Firstly, a systematic review, following the PRISMA guidelines, combined the existing evidence on the association between SES factors and birth outcomes, including low birth weight (LBW), preterm birth (PTB), small for gestational age (SGA), and growth outcomes including stunting, wasting and underweight in children younger than 24 months in SSA countries. Secondly, in a cross-sectional comparative study, the associations between SES factors and birth outcomes in the Democratic Republic of Congo (DRC) and South Africa (SA) were compared in newborns at birth (ranged from 0 to 2 days). Thirdly, a cross-sectional analysis, drawing data from a longitudinal study which is referred to as the Soweto Baby WASH, investigated the associations between SES factors and undernutrition from 0 to 12 months in infants born and living in Soweto in SA. Results: Overall, the thesis highlighted that maternal education and household wealth, as major SES factors, were associated with nutritional status in children at birth and during the first two years of life. Findings were threefold: Firstly, in the systematic review, a lack of consensus on the definition of ‘SES factors’ made comparison and generalisability of the evidence challenging. However, lower HWI, maternal unemployment, and low maternal education were consistently shown to be SES predictors of adverse birth outcomes (LBW, SGA), and infant undernutrition (stunting, wasting, and underweight) in SSA. Secondly, the local/regional context matters when assessing the association between SES factors and infant growth. Living in SA as compared to the DRC was associated with reduced odds of a newborn to be LBW, PTB or SGA, which reflects country-specific differences in maternal and household resources as well as social position (education access, housing, marriage). Being married in the DRC was associated with decreased likelihood of having LBW and PTB newborn whilst South African mothers with secondary level of education and above experienced lower risk of having a SGA newborn. Thirdly, living in a wealthier household was associated with higher weight-for-height Z-scores and associated with lower height-for-age Z-scores at twelve months. However, living in a poor household with mother who had a secondary level of education and higher was associated with greater linear growth and lower weight gain at twelve months in SA. Maternal income, occupation and marital status were not significantly associated with infant growth in Soweto, in, SA. Discussion: Maternal level of education, marital status, and household wealth were associated with growth and nutritional status from birth to two years of age in SSA with country disparities. These disparities were based on the level of socioeconomic development across different countries in SSA. In addition, maternal biological and country factors were strong predictors of infant growth and nutritional outcomes as they underpin individual and household capabilities. In wealthier households, infants gain weight compared to their height in the nutrition transition context like in South Africa. Conclusion: Social policies should protect single women who are socially and economically deprived before, during, and after pregnancy to improve maternal and child health and nutrition, and to optimize their intergenerational influences. Keywords: Socioeconomic status, birth outcomes, infant growth, undernutrition, sub-Sahara Africa, the Democratic Republic of Congo, South Africa
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2020